330 Insights into Dementia- An Integrated Care Approach to Family Support. (16th September 2019) - McHale, Cathy; McGovern, Martina; Dewergifosse, Josephine; Domsa, Maria; McMahon, Anna; Timmons, Fergus; Greene, Julei; Tobin, Fiona; Bennett, Aine; Donnelly, Myra; Coughlan, Tara; O'Neill, Desmond; et al.
Abstract: Background: The increase in the number of people with dementia in the coming years will be significant and could be as high as 132, 000 people by 2041. There is a growing need for enhanced post diagnostic supports for patients living with dementia and their families. We identified the need for a localised educational resource for families and supportive others attending our specialist memory service Methods: Staff from the Integrated Care Team, Specialist Memory Service and Primary Care were trained by the Alzheimer's Society of Ireland to deliver a 6 week 'Insights Into Dementia' carers course. Tutors and dementia advisors from the Alzheimer's Society of Ireland provided in-depth training prior to course delivery and feedback to the facilitators on a weekly basis. The course included advice and education on Dementia; Changing Relationships, Communication; Responding to changes in behaviour; Nutrition; Engaging in activities; Assisting with personal care and Safety in the home. Families gained advice regarding their self-care needs and learned how to access information and support. All services involved worked together to identify, refer and support families with dementia in the local area. The group took place in an accessible location at a time which accommodated families to attend. Each course attendee completed a questionnaire prior to and after commencing the group. Results: The group has delivered education and support to 48 families to date. Feedback from participants was very positive with self-reported increase in confidence, knowledge and awareness about dementia. Waiting time to access support has significantly decreased. Every course has led to a support group who meet up on a regular basis in their community. Conclusion: This novel collaboration has become a key part of the integrated care pathway we have developed to support people living with dementia and their supportive others in our catchment area. The Integrated Care approach has served to enrich the programme and allow for timely signposting to localised supports.